Different kinds of minds contribute to society - Grandin, Temple (Henry Stewart Talks, 2014)
Different minds may process information differently, When does normal variation become an abnormality?, Genetics of personality traits are like a music mixing board, Brain scans – Auditory, Axon projection field much less organized, Abnormalities in left hemisphere, Develop talents in the individual’s specialist brain, Evidence for two types of visualizers, Two categories of mathematicians, Pattern thinking, spatial visualizer, The most obvious is the least obvious, the value of humanities in university curriculum, Animals see details, Animals also “watch” with their ears for potential danger, In humans, language covers up sensory based thinking, bottom up thinking, Teach concepts with multiple examples, associative thinking, How to categorize problems when troubleshooting in both industry and schools, Dogfooding stops too much top down thinking, Tips for helping kids who are different to succeed, Kids doing projects and playing games where the rules and duties are negotiated teaches valuable social skills, Taking hands-on classes out of the schools is really bad, Emphasize developing the area of strength, On-line resources, Show kids interesting things, Learning reading in children, People need to touch in order to perceive, Mentors are essential, We need to get back to doing real stuff, Employer priorities for college graduates, Keys to successful employment on the autism spectrum – Sensory processing disorder occurs with many other disorders (co-morbid), Auditory processing problems, Attention shifting slowness, Structural MRI connections, Accommodations in the work place, It takes a village to raise a child